Here is an example of how to do the work :)
Explanation:
Simplify the following algebraic expressions.
- 6x + 5 + 12x -6
2(x - 9) + 6(-x + 2) + 4x
3x2 + 12 + 9x - 20 + 6x2 - x
(x + 2)(x + 4) + (x + 5)(-x - 1)
1.2(x - 9) - 2.3(x + 4)
(x2y)(xy2)
(-x2y2)(xy2)
Group like terms and simplify.
- 6x + 5 + 12x -6 = (- 6x + 12x) + (5 - 6)
= 6x - 1
Expand brackets.
2(x - 9) + 6(-x + 2) + 4x = 2x - 18 - 6x + 12 + 4x
Group like terms and simplify.
= (2x - 6x + 4x) + (- 18 + 12) = - 6
Group like terms and simplify.
3x2 + 12 + 9x - 20 + 6x2 - x
= (3x2 + 6x2) + (9x - x) + (12 - 20)
= 9x2 + 8x - 8
Expand brackets.
(x + 2)(x + 4) + (x + 5)(- x - 1)
= x2 + 4x + 2x + 8 - x2 - x - 5x - 5
Group like terms.
= (x2 - x2) + (4x + 2x - x - 5x) + (8 - 5)
= 3